Proton pump inhibitors enhance chemosensitivity, promote apoptosis, and suppress migration of breast cancer cells - Ihraiz Worood G.; Ahram Mamoun; Bardaweel Sanaa K. (Acta Pharmaceutica)
Breast cancer is the most common cancer and is the leading cause of cancer deaths among women worldwide. Despite the availability of numerous therapeutics for breast cancer management, cytotoxicity and emergence of drug resistance are major challenges that limit their benefits. The acidic microenvironment surrounding tumor cells is a common feature inducing cancer cell invasiveness and chemoresistance. Proton pump inhibitors (PPIs) are one of the most commonly prescribed drugs for the treatment of acid-related conditions. PPIs have been reported to exhibit antitumorigenic effects in many cancer types. In this study, the anti-proliferative and anti-migratory effects of PPIs in three breast cancer cell lines; MCF-7, T47D, and MDA-MB-231 cells, have been investigated. In addition, the combined effects of PPIs with anticancer drugs, as well as the mechanism of PPI-mediated anti-proliferative activity were evaluated. The anti-proliferative and combined effects of PPIs were evaluated by MTT assay. Cell migration was assessed using the wound-healing assay. The mechanism of cell death was assessed using annexin V-FITC/propidium iodide staining flow cytometry method. Our results indicated that PPIs treatment significantly inhibited the growth of breast cancer cells in a dose-dependent manner. The antiproliferative activity of PPIs was significantly induced by apoptosis in all tested cell lines. The combined treatment of PPIs with doxorubicin resulted in a synergistic effect in all cell lines, whereas the combined treatment with raloxifene exhibited synergistic effect in T47D cells only and additive effects in MDA-MB-231 and MCF-7 cells. In addition, PPIs treatment significantly reduced cell migration in MDA-MB-231 cells. In conclusion, the addition of PPIs to the treatment regimen of breast cancer appears to be a promising strategy to potentiate the efficacy of chemotherapy and may suppress cancer metastasis.